HADIST PENCIPTAAN PEREMPUAN DARI TULANG RUSUK (Analisis-Kritis Terhadap Pandangan Feminis) - Ryandi Ryandi (UIN Sumatera Utara, 2019)
This paper examines further the hadith about the creation of women from the ribs by displaying various related hadith texts, the men-takhrij sanad, analyzing their matan through the comments of the authoritative scholars. This is based on the assumption of feminists that the hadith is a gender bias or